A review of the literature on the economics of drying and milling of padi in Malaysia. - Chew, T.A.; Loo, K.F. (1985)
There are many studies on the technical and engineering aspect of drying and milling of padi in Malaysia. However, there is little work done on economic aspects of these postharvest activities. one such rare piece of work is the study by Soo Lip Tan on the optimum size, number and location of padi driers in the MUDA area. This paper reviews that work and examines the assumption and conclusions in that study. The present spatial distribution of driers is compared with the distribution recommed. Reasons are given to explain the discrepancy between the actual and recommended. situations. One critical question arising thereof is the question of "optimum drying" of padi prior to milling. It would seem that question was never asked in Soo's work or elsewhere for that matter. The implicit assumption is made that the technical optimum drying must be the economic optimum. An attempt is made to estimate the economic optimum.